2021
DOI: 10.1007/s10339-021-01050-5
|View full text |Cite
|
Sign up to set email alerts
|

Brains in space: the importance of understanding the impact of long-duration spaceflight on spatial cognition and its neural circuitry

Abstract: Fifty years after the first humans stepped on the Moon, space faring nations have entered a new era of space exploration. NASA’s reference mission to Mars is expected to comprise 1100 days. Deep space exploratory class missions could even span decades. They will be the most challenging and dangerous expeditions in the history of human spaceflight and will expose crew members to unprecedented health and performance risks. The development of adverse cognitive or behavioral conditions and psychiatric disorders du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Clinically significant neuro-ophthalmological symptoms (e.g., globe flattening, decreased visual acuity, and increased intracranial pressure) have also been reported in long-duration missions, coined under the term Spaceflight-Associated Neuro-Ocular Syndrome (SANS) ( Paez et al, 2020 ). Numerous forms of spaceflight-related structural brain changes are proven, caused by the lack of hydrostatic pressure under microgravity, including upward shift of the brain, upward cerebrospinal fluid shift, ventricular volume gray matter volume decline (for a detailed review see Stahn and Kühn, 2021 ; Roy-O’Reilly et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically significant neuro-ophthalmological symptoms (e.g., globe flattening, decreased visual acuity, and increased intracranial pressure) have also been reported in long-duration missions, coined under the term Spaceflight-Associated Neuro-Ocular Syndrome (SANS) ( Paez et al, 2020 ). Numerous forms of spaceflight-related structural brain changes are proven, caused by the lack of hydrostatic pressure under microgravity, including upward shift of the brain, upward cerebrospinal fluid shift, ventricular volume gray matter volume decline (for a detailed review see Stahn and Kühn, 2021 ; Roy-O’Reilly et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial updating, path integration, route learning, way-finding, and cognitive mapping are key to successfully navigating in novel small- and large-scale environments ( Wolbers and Wiener, 2014 ). The criticality of encoding representations about self-to-object relations and integrating this information into a spatial map of the environment for spaceflight operations was highlighted during the Apollo 14 mission ( Stahn and Kühn, 2021 ). Performance monitoring of astronauts should therefore include tasks assessing the encoding, processing, storage, and retrieval of visuospatial information.…”
Section: Level 1 Priority Recommendationsmentioning
confidence: 99%
“…Moreover, as for any disease and treatment, genotypic and demographic variability within rare diseases further reducing the population that can be targeted with a given therapy, as patients may have vastly different responses to treatments 40 . Of the articles we reviewed, the median [interquartile range] study sample size for astronaut health was 13 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] participants while the median rare disease sample size was 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Despite the low incidence rate of rare diseases, cross-national collaboration and extensive database information can allow rare disease researchers to obtain larger sample sizes.…”
Section: The Sample Size Issue: How Small Is Small?mentioning
confidence: 99%
“…Initial studies have shown an association of one-carbon metabolism pathway polymorphisms with ophtalmic changes 7,8 , which could lead to potential terrestrial prevention strategies 7 . From a neurovestibular perspective, the changes in gravity fields may also cause a decline in the ability of astronauts to orient in the surrounding 9 , a phenomenon similar to the one experienced by individuals affected by a rare familial 1 Astronauts, Life Sciences and Space Medicine Canadian Space Agency, Government of Canada, Longueil, Canada. 2 Molecular and Human Genetics, Baylor College of Medicine, Houston, TX, USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation